Corrosion protection mechanism of Ce3+/polyethylene glycol systems inhibitors for mild steel in sulfate solution - boudellioua, H; Hamlaoui, Y; Pedraza, F (Materials and corrosion, 2023)
In the present paper, cerium nitrate salt was used as a green inhibitor to improve the corrosion resistance of mild steel in 0.1 M Na2SO4 solution. To increase the barrier effect and film stability of the protective layer, polyethylene glycol (PEG) was added. The corrosion tests were evaluated using d.c polarization techniques and electrochemical impedance spectros copy. The composition and morphology of the sample surface were characterized using Raman spectroscopy and MEB/EDS analysis. The resultsshow that the presence of PEG improved relatively the corrosion resistance of mild steel due to the removal of cracks, the pores blocking the formed film and the enhancement of adhesion and compactness of the cerium‐based film. Consequently, the protective film became more coherent on the steel surface. Furthermore, the potentiodynamic polarization indicated that the Ce3+/PEG system behaved as a mixed‐type inhibitor with the dominant effect of the cathodic part.